Tingkat Stres Ibu Menyusui dan Pemberian Asi pada Bulan Pertama - Zuly Daima Ulfa; Yuli Setyaningsih (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2020)
ENGLISHStress on maternal can inhibit breastmilk production so that it disrupts lactation. Stress occurs in the first month after birth delivery as the adaptation of new roles. This condition causes mother give up on breastfeeding early and it affects the sustainibility of exclusive breastfeeding as ideal nutrition for infant. The aim of the study was to analyze the relationship between stress levels of breastfeeding mothers and behavior of giving the breast milk in the first month. This study used a cross sectional approach which was carried out in the working area of Community Health Center of Tayu I. The sampling technique was  purposive sampling. The results showed that breastfeeding mothers who suffered from stress in the first month were as many as 42.5%, consisting of 25% mild stress, 15% moderate stress and 2.5% severe stress. Breastfeeding in the first month was as many as 75%, carried out by mothers not sufferring stress and those suffering mild and moderate stress. The results of chi square analysis obtained ρ 0.041 which means that there was a correlation between stress levels of breastfeeding mothers in the first month. The Odds Ratio (OR) was as many as 9,33 (95% Cl= 1,38,63,20) which means that mothers who suffered from moderate-high level of stress had as many as 9,33 times of possibility not to breastfeeding in the first month. Breastfeeding mothers who did not suffer from stress and suffer mild level of stress were more likely to keep breastfeeding in the first month. INDONESIAStres pada ibu dapat menghambat pengeluaran ASI. Stres sering dialami pada bulan pertama setelah persalinan sebagai adaptasi menjalankan peran baru. Keadaan tersebut dapat membuat ibu berhenti menyusui lebih awal yang berpengaruh pada keberlangsungan pemberian ASI Eksklusif sementara ASI adalah nutrisi terbaik bagi bayi. Tujuan penelitian untuk menganalisis hubungan tingkat stres ibu menyusui dengan pemberian ASI pada bulan pertama. Penelitian ini menggunakan pendekatan cross sectional, dilakukan di wilayah kerja Puskesmas Tayu I. Teknik pengambilan sampel dilakukan secara  sampling purposive. Hasil penelitian menunjukkan ibu menyusui pada bulan pertama yang mengalami stres sebanyak 42,5%; terdiri stres ringan 25%; stres sedang 15%; dan stres berat 2,5%. Pemberian ASI pada bulan pertama sebesar 75%, dilakukan oleh ibu yang tidak mengalami stres maupun ibu yang mengalami stres ringan dan sedang. Berdasarkan analisis chi square didapatkan ρ 0,041; yang berarti ada hubungan tingkat stres ibu menyusui dengan pemberian ASI pada bulan pertama. Odds Ratio (OR) sebesar 9,33 (95% CI=1,38, 63,20) yang berarti ibu dengan tingkat stres sedang-berat mempunyai kemungkinan 9,33 lebih besar untuk tidak memberikan ASI pada bulan pertama. Ibu menyusui yang tidak mengalami stres atau mengalami stres dalam fase ringan mempunyai kemungkinan lebih besar untuk tetap melakukan pemberian ASI pada bulan pertama.